2002
DOI: 10.1007/bf03165129
|View full text |Cite
|
Sign up to set email alerts
|

Non-myeloablative hematopoietic cell transplant for treatment of nonmalignant disorders in children

Abstract: Hematopoietic stem cell transplantation (HCT) may offer the only curative therapy for certain life-threatening immune deficiency disorders. Conventional HCT poses a risk to patients for severe morbidity, mortality, and late sequelae resulting from myeloablative preparative regimens. This review summarizes the development of nonmyeloablative regimens that have the potential to reduce both short- and long-term risks of HCT. Results of NM-HCT in a small number of patients indicate that this procedure may play an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Sustained engraftment and alleviation of clinical phenotype has been reported in patients with SCD and thalassemia with reduced intensity conditioning regimen [25][26][27][28][29][30]. HCTs using NMA regimens, although well tolerated, have generally not resulted in stable engraftment [31][32][33].…”
Section: Alternative Donors and Conditioning Regimenmentioning
confidence: 99%
“…Sustained engraftment and alleviation of clinical phenotype has been reported in patients with SCD and thalassemia with reduced intensity conditioning regimen [25][26][27][28][29][30]. HCTs using NMA regimens, although well tolerated, have generally not resulted in stable engraftment [31][32][33].…”
Section: Alternative Donors and Conditioning Regimenmentioning
confidence: 99%
“…48 Regimens with 'reduced toxicity' (Fig. Recent reports have suggested that non-myeloablative (NM) SCT may be a suitable alternative to achieve stable engraftment of immunocompetent donor cells with reduced procedure-related morbidity and mortality.…”
Section: Non-myeloablative Sctmentioning
confidence: 99%
“…Nonmyeloablative BMT is likely to be safer in terms of long-term outcome and complications, although this remains to be demonstrated. 2,8 Our experience suggests that this approach is a safe alternative method for achieving hematopoietic chimerism in selected patients with DBA. …”
mentioning
confidence: 96%
“…[1][2][3][4] Diamond-Blackfan anemia (DBA) is a childhood disorder characterized by normochromic-macrocytic anemia, reticulocytopenia and normocellular bone marrow with a selective deficiency of erythroid progenitors. 5 Most patients initially respond to corticosteroids, but about 60% of patients require chronic red cell transfusions and die from hemosiderosis in the second or third decade of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation